The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1086/522847
|View full text |Cite
|
Sign up to set email alerts
|

One‐Sided Ejaculation of Echidna Sperm Bundles

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 4 publications
3
23
0
Order By: Relevance
“…Monotremata: In Tachyglossus aculeatus, the bifid penis is anatomically symmetric, but in erection, one half is retracted, making it functionally asymmetric (Johnston et al 2007) Marsupialia: Symmetric (Prasad 1974 (Prasad 1974) Phylum Chordata: Reptilia Squamata: all snakes have unequal hemipenes. In gartersnakes, Shine et al (2000) found that the right hemipenis was slightly wider than the left.…”
Section: Phylum Chordata: Mammaliamentioning
confidence: 99%
“…Monotremata: In Tachyglossus aculeatus, the bifid penis is anatomically symmetric, but in erection, one half is retracted, making it functionally asymmetric (Johnston et al 2007) Marsupialia: Symmetric (Prasad 1974 (Prasad 1974) Phylum Chordata: Reptilia Squamata: all snakes have unequal hemipenes. In gartersnakes, Shine et al (2000) found that the right hemipenis was slightly wider than the left.…”
Section: Phylum Chordata: Mammaliamentioning
confidence: 99%
“…2002); rat (Immler et al, 2007); and echidna (Johnson et al, 2007)]. Spermatozoan conjunction is found also among invertebrate phyla, with most examples being listed in a paper by Ishijima et al (Ishijima et al, 1999).…”
Section: M Woolley and Othersmentioning
confidence: 99%
“…The sperm heads are thus considered rather fragile as there is no capacity for the formation of stable crosslinked nuclear protein-DNA complexes. Presumably platypus and echidna spermatozoa typically ascend the female tract as motile bundles (Johnston et al, 2007;Nixon et al, 2016), and although relatively little is known about fertilization mechanisms, it is interesting to see that the platypus genome encodes each of the four proteins of the human zona pellucida. Field and captive observations of echidna reproduction (Nicol and Andersen, 2007;Rismiller and McKelvey, 1996) have shown that the egg is incubated in the pouch for approximately 10 days after a pregnancy of about 3 weeks, whereupon the female eventually deposits the young in a nursery burrow.…”
Section: Monotremesmentioning
confidence: 99%
“…The echidna penis itself is most bizarre, being about a quarter of the animal's body length when erect and terminating in two sides, each side possessing a glans penis taking the form of 2 rosettes. The urethrae terminate on the surfaces of the rosette in a series of openings through which the semen emerges (Johnston et al, 2007); the platypus penis is equally bizarre and appears adapted for securing this organ into the urogenital sinus of the female during mating, which occurs in the water column.…”
Section: Monotremesmentioning
confidence: 99%